ANALISIS RESIKO KECELAKAAN KERJA DENGAN METODE HIRARC (Studi Kasus : CV. XYZ) - Husna, Fasha; Donoriyanto, Dwi S. (LPPM Universitas Bina Bangsa, 2024)
In the production process, there is a potential risk of work accidents that can arise due to the production activities themselves, both due to worker negligence and work environment conditions. Based on observations of production activities at CV. XYZ and interviews with several workers, various risks of work accidents were identified, both related to the production process and environment. This paper was prepared using qualitative analysis that utilizes data analysis through the HIRARC method. Proposed improvements regarding the risk of accidents were prepared using the 5W+1H method. The results of the analysis show that the main factors for the emergence of work accidents are rooted in the aspects of machines and people. From the accident risk level discovery process, nine hazard risks were categorized based on the emergence factors and related activities. The assessment provided information that the risk level varied from high to low. To address this, the proposed improvements focus on the five occupational accident risks with the highest risk levels, namely: Complete use of PPE (Personal Protective Equipment) and maintaining a safe distance from the machine, Conducting regular machine checks and ensuring procedures are carried out correctly, Providing briefings from the division head to employees to focus, comply with SOPs, and follow a good work schedule, Educating workers on the importance of using PPE and work safety, Installing hazard signs in risky areas, such as where materials have the potential to fall.